G2019S Variation in LRRK2: An Ideal Model for the Study of Parkinson’s Disease? - Ren, Chao; Ding, Yu; Wei, Shizhuang; Guan, Lina; Zhang, Caiyi; Ji, Yongqiang; Wang, Fen; Yin, Shaohua; Yin, Peiyuan (Frontiers in Human Neuroscience, 2019)
Parkinson's disease (PD) is the second largest neurodegenerative disorder that has plagued human beings for more than 200 years. The etiology and detailed pathogenesis of PD is unclear, which is currently believed the result of the interaction between genetic and environmental factors. Studies have found that PD patients with LRRK2:G2019S variation have the typical clinical manifestations of PD, which may be familial or sporadic, and have the age-dependent pathogenic characteristics. Therefore, it may be an ideal model to study the interaction of multiple factors such as genetic, environmental and natural aging factors in PD in the future. This article reviewed the progress of LRRK2:G2019S study in the research of PD in order to provide new research ideas and directions for the pathogenesis and treatment of PD.